The effect of acupuncture combined with hyperbaric oxygenation compared with hyperbaric oxygenation alone for patients with traumatic brain injury: a systematic review and meta-analysis - Li, Geng; Wang, Binyang; Fan, Shuochen; Liu, Shuangli; Shao, Lu; Li, Chuanxiong; Fang, Yongjiang; Li, Jianfeng; Qiu, Meihua; Zhang, Yuping; Pan, Lei (Frontiers in Neurology, 2025)
ObjectiveThis study aimed to evaluate the effects of acupuncture combined with hyperbaric oxygenation (HBO) compared with HBO alone in improving the disturbance of consciousness (DOC) of people with traumatic brain injury (TBI).MethodsThe Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed in this study. In accordance with the preestablished search strategy, all the literature was obtained from eight online databases. Following the stringent application of inclusion and exclusion criteria, two researchers conducted an independent extraction of valid data from eligible randomized controlled trials (RCTs). The risk of bias in each study was assessed using the Cochrane Risk of Bias 2.0 tool. The meta-analysis was conducted utilizing the RevMan software. Adverse events were determined based on data from each study assessing the safety of acupuncture treatment.ResultsA total of 11 RCTs with 896 participants were included in the analysis. Overall, the methodological quality of the RCTs encompassed within this meta-analysis was below standard. The pooled data demonstrated that acupuncture treatment combined with HBO was significantly superior to HBO alone, based on the Glasgow Coma Scale (GCS) scores [mean difference (MD) = 2.13, 95% confidence interval (CI): 1.64–2.62, p < 0.00001]. We also found that electroacupuncture (EA) combined with HBO improved GCS scores more than HBO alone in TBI patients (MD = 2.15, 95% CI: 1.95–2.36). The early intervention (MD = 3.09, 95% CI, 2.66–3.52) demonstrated significantly more significant improvement in GCS scores following combination therapy compared with the late intervention group (MD = 1.86, 95% CI, 1.47–2.25). Furthermore, compared with HBO alone, acupuncture combined with HBO significantly improved patients’ consciousness rate (CR) (RR = 2.26, 95% CI: 1.48–3.46). Statistical analysis also revealed that acupuncture combined with HBO improved the effective rate (ER) (RR = 1.47, 95% CI: 1.27–2.69). Additionally, no studies reported any significant adverse events.ConclusionCompared with HBO alone, acupuncture combined with HBO has a more substantial positive effect on GCS scores, AR, and ER in patients with TBI. However, given the limited availability of high-quality evidence and the dearth of RCTs in this area, the conclusions drawn herein warrant validation through additional research endeavours.Clinical trial registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024576067, CRD42024576067.